2019
DOI: 10.1111/jvim.15403
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an HMGA2 variant for pleiotropic effects on height and metabolic traits in ponies

Abstract: Background Ponies are highly susceptible to metabolic derangements including hyperinsulinemia, insulin resistance, and adiposity. Hypothesis/Objectives Genetic loci affecting height in ponies have pleiotropic effects on metabolic pathways and increase the susceptibility to equine metabolic syndrome (EMS). Animals Two hundred ninety‐four Welsh ponies and 529 horses. Methods Retrospective study of horses phenotyped for metabolic traits. Correlations between height and metabolic traits were assessed by Pearson's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 67 publications
(73 reference statements)
7
28
3
Order By: Relevance
“…As a core transcription factor in embryonic stem cells, ZNF281 (zinc finger protein 281) was found to be related to spontaneous osteochondrogenic differentiation [38]. Other studies showed the strong association of LCORL/NCAPG, HMGA2, PROP1, LASP [39], ZFAT, DIAPH3 [40], ACTN2, ADAMTS17, GH1, ANKRD1 [40], and ACAN [41,42] with miniature size and dwarfism in a variety of pony breeds, including Shetland [41,43], miniature [44], Welsh ponies [45], German warmblood horses [46], American miniature horses, Brazilian ponies [47], and Jeju ponies [48], as well as B4GALT7 [49] and PROP1 [50] in Friesian horses. These genes were not found in this study, which may be due to the expression specificity of lncRNAs in different horse breeds [27] and different omics levels, since TBX3, under strong selection in Chinese ponies, was also identified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…As a core transcription factor in embryonic stem cells, ZNF281 (zinc finger protein 281) was found to be related to spontaneous osteochondrogenic differentiation [38]. Other studies showed the strong association of LCORL/NCAPG, HMGA2, PROP1, LASP [39], ZFAT, DIAPH3 [40], ACTN2, ADAMTS17, GH1, ANKRD1 [40], and ACAN [41,42] with miniature size and dwarfism in a variety of pony breeds, including Shetland [41,43], miniature [44], Welsh ponies [45], German warmblood horses [46], American miniature horses, Brazilian ponies [47], and Jeju ponies [48], as well as B4GALT7 [49] and PROP1 [50] in Friesian horses. These genes were not found in this study, which may be due to the expression specificity of lncRNAs in different horse breeds [27] and different omics levels, since TBX3, under strong selection in Chinese ponies, was also identified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the 662 kb long ROH island on ECA6 in Exmoor Pony at position 81.12-81.80 Mb harboring the genes HMGA2 , LLPH , IRAK3 and HELB supports these considerations. Norton et al [83] identified ancestral haplotypes between ECA6:81.16-81.58 associated with height and baseline insulin values in Welsh ponies and supposed HMGA2 and IRAK3 as candidate genes involved in the equine metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Several genome-wide association studies (GWAS) have outlined HMGA2 as an important factor in determining dimensions in humans, horses and dogs [90][91][92][93][94][95][96][97][98][99][100][101]. Furthermore, Hmga2 mutations have been involved in Silver-Russell syndrome (SRS), or SRS-like syndromes [102][103][104], or ear dimensions in pigs [105].…”
Section: Hmga Dysregulation and Its Impact On Body Sizementioning
confidence: 99%